Individual and Community Strategies in Public Issues - Long, Jonathan (My University, 1975)
This paper aims to produce a paradigm of community dissent. The main argument revolves around the actions of residents who are dissatisfied with either the conditions in their neighbourhood, or with proposed changes to it. Thus far fundamental types of strategies are identified for such residents and these take the form of 'exit', 'voice', 're'signation' and 'outlaw activity'.
In using a conflict approach, the constraints which bear upon the initial choice decision and subsequent implementation of the strategies are constantly emphasised. The strategies and their attendant constraints then form the basis for the construction of a dynamic model with which to view the development of community conflicts.
In order to provide some substantive basis for the assertions made in the model the major hypotheses derived from the model are tested in an empirical example of community conflict in Victoria Park, Hamilton.
Keywords: community dissent; neighbourhood conditions; conflict approach; community development